2023
DOI: 10.1002/ctm2.1130
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights in the pathomechanism of Brugada syndrome and fever‐related type 1 ECG changes in a preclinical study using human‐induced pluripotent stem cell‐derived cardiomyocytes

Abstract: Background Brugada syndrome (BrS) is causing sudden cardiac death (SCD) mainly at young age. Studying the underlying mechanisms associated with BrS type I electrocardiogram (ECG) changes in the presence of fever and roles of autophagy for BrS remains lacking. Objectives We sought to study the pathogenic role of an SCN5A gene variant for BrS with fever‐induced type 1 ECG phenotype. In addition, we studied the role of inflammation and autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Recent literature supports a polygenic mode of inheritance with common and rare genetic variants to exhibit the BrS phenotype [ 4 ]. Premature inactivation/blockade of the Na v 1.5 sodium channel at higher temperatures is associated with a high risk of ST-segment elevation and an increased risk of VF and SCD [ 9 , 10 ]. In patients with BrS, cardiac structural changes involving the right ventricular outflow tract (RVOT) are also noted [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature supports a polygenic mode of inheritance with common and rare genetic variants to exhibit the BrS phenotype [ 4 ]. Premature inactivation/blockade of the Na v 1.5 sodium channel at higher temperatures is associated with a high risk of ST-segment elevation and an increased risk of VF and SCD [ 9 , 10 ]. In patients with BrS, cardiac structural changes involving the right ventricular outflow tract (RVOT) are also noted [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certain environmental factors that can influence the type 1 EKG phenotype include temperature, medications (sodium channel blockers (SCB)), electrolyte disturbances (hypokalemia, hyperkalemia, and metabolic acidosis), infections, and illicit drug use like cocaine [ 7 , 9 , 12 ]. In particular, hyperthermia can trigger VF and cause cardiac arrest in patients with a diagnosis of BrS; it can also induce a Brugada type 1 EKG pattern in patients without a prior diagnosis of BrS [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…They reported increased channel sensitivity to high temperature and lipopolysaccharide challenge in hiPSC-CMs from a BrS cell line with this variant but not in two non-BrS hiPSC-CM lines. They also suggested that lipopolysaccharides may exacerbate the BrS phenotype by enhancing autophagy, whereas fever may exacerbate the BrS phenotype by inhibiting PKA signaling in BrS cardiomyocytes [149]. SCN5A-1795insD leads to an overlap syndrome, in which patients present with both features of BrS and cardiac conduction disease (decreased I Na ) and long QT syndrome type 3 (increased late I Na ).…”
Section: Scn5amentioning
confidence: 99%